OPTIMIZING STOCK TRADING PERFORMANCE: LEARNING TECHNICAL AND FUNDAMENTAL ANALYSIS USING "SHARIA PROFITS" - Subqi, Tajus (Jurnal As-Salam, 2024)
The rapid development of the Islamic capital market in Indonesia requires a deep understanding of fundamental and technical analysis. Through the learning and application of "Profits Syariah," it is hoped that the quality of trading by students at the Faculty of Islamic Economics and Business (FIEB) at Annuqayah University in Guluk-Guluk Sumenep can be improved, supporting effective Sharia investment practices. This research aims to explore, evaluate, and analyze in depth the concepts of technical and fundamental learning, as well as the optimization of the role of this learning in improving stock trading performance using the "Profits Syariah" application at the Faculty of Islamic Economics and Business at Annuqayah University in Guluk-Guluk Sumenep. It is descriptive qualitative research with a case study approach, using interview sheets distributed via Google Form to students of Islamic Economics (IE) and Islamic Banking (IB) programs who have taken Sharia Capital Market courses in the 5th and 7th semesters. Out of 130 students, 79 met the criteria, with 5 to 10 students having similar answers for each interview question after filtration. Direct interviews were conducted with the course instructors and program coordinators. Qualitative data analysis was performed using the Miles and Huberman method. The research results show that first, learning fundamental and technical analysis in the Islamic capital market using the Student-Centered Learning (SCL) and Experience Learning (EL) methods is effective, making students actively develop analytical skills, making learning more exciting and modern, and preparing them as competent and ethical financial professionals. Second, this learning is efficacious in improving stock trading performance, as indicated by interview results related to learning effectiveness indicators in improving stock trading performance.